Validity and Practicality of the Learning Implementation Plan And Student Worksheet with Make A Match Learning Model and Practicum Method on Fungi Material - Fatma, Fatma; Hasan, Ani Mustapa; Latjompoh, Masra (Universitas Labuhanbatu, 2022)
The learning implementation plan and student worksheet that are lacking in terms of the learning process cause the learning process to be less efficient, so it is necessary to develop the learning implementation plan and student worksheet. The purpose of this study is to determine the validity and practicality of The learning implementation plan and student worksheet with a make a match learning model and practicum methods on mushroom material. The research method uses a modified type of R&D research in Sugiono 2018. The results of this study show that the learning implementation plan & student worksheet as seen from the validation results by two expert validator lecturers obtained as a percentage of The learning implementation plan scores of 89% and the student worksheet were 94% obtained very valid criteria and from practitioner validators, namely one teacher obtained as a percentage of the learning implementation plan scores of 94% and student worksheet 80%. The practicality of The learning implementation plan and student worksheet can be seen from: a) the results of the implementation of learning at meetings I, II, and III obtained as an average score percentage of 93.06%. b) the activities of the learners at meetings I, II, and III obtained a percentage of the average score of 97.15% and c) the response of the learners obtained as an average score percentage of 81.50% with excellent criteria. Based on the results of the study, it can be concluded that the learning implementation plan and student worksheet with the make a match learning model and the mushroom material practicum method are declared valid and practical for use in the learning process